Authentication of sheep (Ovis aries) and goat (Capra hircus) meat species using species-specific polymerase chain reaction - GIRISH, P S; VAITHIYANATHAN, S; KARABASANAVAR, NAGAPPA; BAGALE, SHAILESH (The Indian Journal of Animal Sciences, 2016)
Small ruminants (sheep and goat) immensely contribute to the Indian meat food basket; yet regional preference for either sheep or goat meat varies. Owing to the differences in the market prices, these two closely resembling species meats are often misrepresented interchangeably. Prevention of such fraudulent practices requires authentic and sensitive speciation tools. A novel mitochondrial D-loop based species-specific polymerase chain reaction (PCR) technique was developed for the precise detection of origin of sheep and goat meats. Species-specific primers (SSP-G and SSP-S) developed for PCR in this study amplify 229 and 425 base pairs products specific to goat and sheep species. An additional herteroplasmic PCR product of size 350 bp was evident only in sheep. Primers designed in this study were checked for the absence of cross-species amplification in closely related animal species and was successfully applied for the authentication of a forensic case. Our results indicated prerogative applications of the novel species-specific PCR for the authentic identification of origin of sheep and goat species thereby aiding in the prevention of the menace of misrepresentation of meats.